(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
ينتشر القشري برغوث الماء العذب Daphnia lumholtzi في الجزء الجنوبي من الكرة الأرضية عموماً، وسجل وجوده في شمال القارة الأمريكية وشمال شرق أفريقيا واستراليا وكذلك في البرازيل والهند والقوقاز والعراق وتركيا. جمعت العينات من مياه برك تربية الأسماك في منطقة الغاب خلال صيف 2006-2007م، وسجل وجود أفراد الـنوع lumholtzi Daphnia لأول مرة في هذه الدراسة. وتتميز أفراد هذا النوع عن بقية أنواع الجنس Daphnia بوجود قبعة طويلة وشوكة للدرقة طويلة أيضاً، إضافة إلى وجود امتدادين جانبيين على الناحية الخلفية للرأس. وتطابقت الصفات التصنيفية الشكلية والتشريحية مع صفات الأنواع المسجلة في المناطق المذكورة أعلاه. تم معالجة العينات وعزلت منها ، ووصل عددها إلى 34 فرداً معظمها من الإناث الناضجة والقليل منها حاملات لمحافظ البيض.ولم يسجل في العينات ظهور أية ذكور. Daphnia Lumholtzi (water flea) is distributed in the southern part of the globe in general. It is recorded in north America, north-east Africa, Australia, Brazil, Caucasus region, Iraq and Turkey. The specimens are collected from fish-farming ponds of Alghab during the summers of 2006-2007, and treated as a newly recorded species in Syria. The differences between this species and others is very distinct. It has a long helmet and a long spine-tail, in addition to the presence of fornices in the posterior part of the head. The morphological and anatomical characteristics are similar to those species recorded in the regions mentioned above. The specimens are treated and 34 individuals of female adults are isolated. A few of them carry ephippiums. No males are recorded in specimens.